Hygienic assessment of professional combined risk in case of modern multicomponent pesticides usage on maize and sunflower crops. - T. V. Ruda; M. M. Korshun (Medičnì Perspektivi)
The results of the risk assessment of combined hazard effects of diflufenzopyr, dicamba, nicosulfuron (herbicide Kelvin Plus) and azoxystrobin, difenoconazole (fungicide Amistar Gold 250 SC) on workers involved in working with them are presented. The field study on maize and sunflower crops, in which Kelvin Plus and Amistar Gold were used at maximum flow rates of 0,4 kg/ha and 1,0 l/ha, respectively was performed. During ground handling, the working solution consumption was 300 l/ha, while during aviation – 50 l/ha. Air samples of the working area, washings from the skin, stripes on the overalls of workers were selected, followed by the determination of the residual quantities of the active substances under study in the selected samples. Hazard coefficients and indices, based on exposure and permissible inhalation and percutaneous doses (a. s.) were calculated. It has been established that the working conditions of agricultural workers are permissible, since the hazard indices of the harmful combined effect of the pesticides under study are lower than 1. Before carrying out full-scale studies, the coefficients of possible inhalation poisoning were calculated, and it was established that all pesticides under study are of low risk as for this coefficient – 4 class. An assessment of the possible occurrence of acute toxic effects when working with pesticides was made as well, that is, the selectivity coefficients of the action were determined for inhalation and percutaneous effects on humans. It was established that all investigated a. s. at inhalation influence on the person have sufficient selectivity of action, except for azoxystrobin, which has a low selectivity of action; when applied to the skin all the a. s. have sufficient selectivity of action. The use of the tested combined preparations on maize and sunflower crops does not endanger the workers, while observing the established hygienic regulations.